2022
DOI: 10.3390/microorganisms10091712
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Climatic, and Parasite Molecular Factors Impacting the Incidence of Cutaneous Leishmaniasis Due to Leishmania tropica in Three Moroccan Foci

Abstract: Cutaneous leishmaniasis (CL) occurring due to Leishmania tropica is a public health problem in Morocco. The distribution and incidence of this form of leishmaniasis have increased in an unusual way in the last decade, and the control measures put in place are struggling to slow down the epidemic. This study was designed to assess the impact of climatic and environmental factors on CL in L. tropica foci. The data collected included CL incidence and climatic and environmental factors across three Moroccan foci (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Leishmaniosis is a climate-sensitive disease, since the reproduction and behavior of its vector, the sandfly, is under strong impact of meteorological parameters: precipitation, air temperature, and humidity [24][25][26][27]. Our study demonstrated that per every degree of air temperature rise in the coastal and central region yearly, there was a statistically significant positive correlation with the increase in the number of people affected by leishmaniosis.…”
Section: Discussionmentioning
confidence: 69%
“…Leishmaniosis is a climate-sensitive disease, since the reproduction and behavior of its vector, the sandfly, is under strong impact of meteorological parameters: precipitation, air temperature, and humidity [24][25][26][27]. Our study demonstrated that per every degree of air temperature rise in the coastal and central region yearly, there was a statistically significant positive correlation with the increase in the number of people affected by leishmaniosis.…”
Section: Discussionmentioning
confidence: 69%
“…Climate impacts CL dynamics through its effect on vector population density and ecological behavior; meteorological parameters influence vector reproduction and behavior [ 68 ], with vector abundance linked to CL cases [ 12 ]. Vectors show sensitivity to abrupt temperature changes, suggesting an optimal development temperature range identified in experimental studies across various sandfly and Leishmania species [ 16 , 69 ], which respond differently to environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In other study, the highest rates of both active lesions and scars were found in the age group of 10 years or under with significant differences (Fazaeli et al., 2009). This result can be explained by the fact that the prevalence of the infection tends to increase with age up to 15 years, after which it becomes stable, probably indicating the development of a protective immune status (Daoui et al., 2022).…”
Section: Discussionmentioning
confidence: 99%